Impact of COVID-19 Virus Pandemic on Surgical Practices: rejuvenation - Md Jamal, Abul Bashar (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Abstract not available J Bangladesh Coll Phys Surg 2021; 39: 211-212